Transitional justice in Colombia: challenges and perspectives. A multidisciplinary approach to restoring the social fabric - Prada Galvis, Alberto (DIXI, 2022)
Colombia is currently undergoing a process of reconstruction of the social fabric after the armed conflict. Transitional justice emerges as a legal mechanism and an integral system for the achievement of peace, with the strengthening of civil trust and social restoration. The challenges and perspectives today seek to promote an innovative sense of nation, a new interpretation of the concept of victim and a different vision of the values of the State. The current project aims to interpret the victim as a transforming subject, founder of coexistence strategies and direct participant in actions that materialize real practices of truth, justice and reparation. With a qualitative and multidisciplinary approach, social mapping is applied to obtain data that will allow a systematic analysis of the perspectives and scope of transitional justice from the perspectives of philosophy, anthropolo-gy, sociology, psychology, education and economics. The aim is to establish the historical responsibility of the communities in the reconstruction of the social fabric, and to reinterpret and assume effective commitments to resilience of the population of victims in Barrancabermeja, Yondó and Cantagallo. It is expected that the results will impact the victims in a new reading, involving them proactively and legitimately in their own restoration, with repercussions for the recovery of human capital in the three territories under study.